Perspective of Part-Time Working Grade 12 HUMSS Students of Bestlink College of the Philippines: Its Effects on their Online Classes: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Motivation is a vital component for each student to keep on learning. The challenges they encountered in the new normal Education negatively and positively affected students' academic performance. The result of suddenly changing the learning system has pushed students and teachers to adopt new learning styles. This study aims to identify the Perspective and Challenges of Grade 12 HUMSS Students in New Normal Education at Bestlink College of the Philippines.  The researcher used the qualitative method as the research design. The instrument used for the survey and questionnaire to gather data. The researchers also searched for related literature and studies. A random sampling technique was also used to select the respondents of this study. Based on the answers gathered from the respondents, "Active Online class performance" is the aspect that is mostly affected by the sudden occurrence of new normal education. Students with great support from family, teachers and friends tend to participate easily in class discussions. “Moral and Financial Support" also greatly improves student academic performance. Students without parental or guardians' support are unmotivated and inactive in-class performances. The researchers concluded that the Perspectives and Challenges of selected Grade 12 HUMSS Students in New Normal Education are a low internet connection, online divide and socio-economic status. Lack of concentration, focus and confusion about the priorities of being a grade 12 student are also challenges. Parents or guardians have a big role in the academic aspect of their children. Parents must encourage and support their children morally and financially and spend time communicating and discussing academic priorities. Good communication within the family cycle can positively affect the students' academic performance. Keeping the priorities in focus will result in time-submitted school work. The data will encourage the institution to continue to develop the current status of new normal education and enrich academic and non-academic activities in learning at home more easily.
Keywords: perspective; Challenges; HUMSS; BCP